2005
DOI: 10.1128/mcb.25.8.3305-3316.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Domain in Set2 Mediates RNA Polymerase II Interaction and Couples Histone H3 K36 Methylation with Transcript Elongation

Abstract: Histone methylation and the enzymes that mediate it are important regulators of chromatin structure and gene transcription. In particular, the histone H3 lysine 36 (K36) methyltransferase Set2 has recently been shown to associate with the phosphorylated C-terminal domain (CTD) of RNA polymerase II (RNAPII), implying that this enzyme has an important role in the transcription elongation process. Here we show that a novel domain in the C terminus of Set2 is responsible for interaction between Set2 and RNAPII. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
459
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 448 publications
(501 citation statements)
references
References 45 publications
39
459
2
1
Order By: Relevance
“…Second, Figure 5B confirms that the WW domain-containing construct of Set2 can indeed bind directly to the PCTD. There are thus at least two independent phosphoCTD binding domains in Set2, one encompassed by amino acids 425-551 and the other by amino acids 619-733 (the SRI region; see ref 65). Third, Figure 5C shows that the N-terminal 160 amino acids in Ssd1 are sufficient for phosphoCTD binding.…”
Section: (D) Spr (Biacore) Analysis: Specificity Of Pcaps For Doubly mentioning
confidence: 90%
See 1 more Smart Citation
“…Second, Figure 5B confirms that the WW domain-containing construct of Set2 can indeed bind directly to the PCTD. There are thus at least two independent phosphoCTD binding domains in Set2, one encompassed by amino acids 425-551 and the other by amino acids 619-733 (the SRI region; see ref 65). Third, Figure 5C shows that the N-terminal 160 amino acids in Ssd1 are sufficient for phosphoCTD binding.…”
Section: (D) Spr (Biacore) Analysis: Specificity Of Pcaps For Doubly mentioning
confidence: 90%
“…Recent results lend credence to this hypothesis. For example, as mentioned earlier, deletion of either CTDK-I catalytic activity or the SRI region of Set2 leads to a specific loss of H3 K36 methylation, suggesting that binding of Set2 to the PCTD made by CTDK-I is central to its activity in vivo (37,38,65 (68), and splicing of newly synthesized transcripts can be assayed. In contrast to wild type, in which unspliced precursor is never observed (e.g., Figure 9B, lanes 2 and 3), ctk1Δ cells consistently contain significant amounts of the unspliced RPS17A transcript (lanes 5 and 6).…”
mentioning
confidence: 87%
“…For instance, in yeast, Ser2 phosphorylation of the CTD potentiates interaction with the essential polyadenylation factor Pcf11 (de Vries et al 2000;Barilla et al 2001;Licatalosi et al 2002;Ahn et al 2004). The H3-K36 methyltransferase Set2 binds elongating RNAPII, recognizing the doubly phosphorylated CTD (Ser5/Ser2) (Hampsey and Reinberg 2003;Kizer et al 2005). Interestingly, a genomic analysis employing tilling arrays in mammalian cells showed that H3-K36 methylation often decreases near the poly(A) site during or prior to RNAPII release, leading to the intriguing possibility that H3-K36 methylation plays a role in transcription termination (Lian et al 2008).…”
Section: Ctd Of the Rnapii Large Subunitmentioning
confidence: 99%
“…Set2 interacts with the repeating C-terminal domain (CTD) of RNA polymerase II (RNAPII) (12,(21)(22)(23)(24)(25). In yeast, the CTD of RNAPII consists of 26 repeats of a heptapeptide repeat sequence (YSPTSPS) in which all three serine residues can be phosphorylated (26 -28).…”
Section: Methylation Of Lysine 36 On Histone H3 (H3k36) Is Catalyzed mentioning
confidence: 99%